Expression of multidrug-resistance associated proteins in human retinoblastoma treated by primary enucleation - Tang, Li-Juan (Int J Ophthalmol, 2018)
AIM: To reveal the expression of multidrug-resistance associated proteins: glutathione-S-transferase π (GSTπ), P-glycoprotein (P-gp) and vault protein lung resistance protein (LRP) in retinoblastoma (RB) without any conservative treatment before primary enucleation and to correlate this expression with histopathological tumor features. METHODS: A total of 42 specimens of RB undergone primary enucleation were selected for the research. Sections from the formalin-fixed, paraffin-embedded specimens were stained with HE and immunohistochemistry to detect the expression of GSTπ, P-gp and LRP. RESULTS: GSTπ was expressed in 39/42 (92.86%) RBs and in 9/9 (100%) well-differentiated RBs. P-gp/GSTπ was found in 30 (71.42%) of 42 RBs. Totally 9 (21.43%) tumors were well differentiated and 33 (78.57%) were poorly differentiated. Totally 15 (35.71%) eyes had optic nerve (ON) tumor invasion, 36 (85.71%) had choroidal tumor invasion, and 14 (33.33%) had simultaneous choroidal and ON invasion. There was no statistically significant relationship between P-gp, GSTπ, LRP positivity and the degree of ocular layer tumor invasion and ON tumor invasion (P>0.05). CONCLUSION: RB intrinsically expresses GSTπ, P-gp and LRP. GSTπ expression is positive in 100% well-differentiation ones, so in which way it is correlated with differentiation. But the other two proteins expressions are not related to tumor differentiation and to the degree of tumor invasion. GSTπ may be a new target of chemotherapy in RB.